Hubungan Antara Minat Baca dan Kemampuan Apresiasi Sastra pada Siswa Kelas V SDN 2 Bojongmenteng Kabupaten Lebak - Yoma Hatima (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to determine the relationship between reading interest and literary appreciation ability in fifth grade students at SDN 2 Bojongmenteng, Lebak Regency. The background of this study is based on the fact that low reading interest in students often results in a lack of ability to appreciate literary works, such as poetry, fairy tales, and folk tales. Literary appreciation requires emotional and intellectual involvement that is closely related to reading habits. This study uses a quantitative approach with a correlational method. The subjects of the study were all 30 fifth grade students. The instruments used were a reading interest questionnaire and a literary appreciation ability test that had been validated by experts. The results of data analysis using the Pearson correlation test showed a positive and significant relationship between reading interest and literary appreciation ability with a correlation coefficient value of 0.678 and a significance of 0.001 <0.05. This shows that the higher the students' reading interest, the better their ability to appreciate literary works. This study recommends that teachers increase literacy activities through integrated reading activities and provide stimuli in the form of literary works that are appropriate to the students' development level. This finding provides a basis that strengthening reading interest needs to be a focus in learning Indonesian, especially in the literary aspect.